Right ventricular function and outcome in patients undergoing transcatheter mitral valve repair. (3rd October 2022) - Koschutnik, M; Dona, C; Nitsche, C; Dannenberg, V; Koschatko, S; Mascherbauer, K; Beitzke, D; Loewe, C; Huelsmann, M; Schneider, M; Bartko, P; Goliasch, G; et al.
Abstract: Objectives: This study sought to assess the impact of right ventricular dysfunction (RVD) on event-free survival after transcatheter mitral valve repair (TMVR) for severe mitral regurgitation. Background: The prognostic value of left and RV global longitudinal strain (LV- and RV-GLS) on cardiovascular magnetic resonance feature tracking (CMR-FT) in patients undergoing TMVR is unknown. Methods: Consecutive TMVR patients underwent pre-procedural and follow-up CMR-FT analysis. Kaplan-Meier estimates and multivariable Cox-regression analyses were performed, using a composite endpoint of heart failure hospitalization (HFH) and death. Results: 62 patients (78.3±7.0y/o, 45% female, EuroSCORE-II: 9.6±7.1%) underwent CMR-FT prior to TMVR, 24% had concomitant tricuspid edge-to-edge repair (TTVR). On presentation, 23 (37%) patients suffered RVD, defined as RV-GLS >−20% on CMR-FT. RVD was associated with reduced LV and RV ejection fraction (LVEF: 39.2 vs. 48.7%, p=0.008, RVEF: 35.1 vs. 46.7%, p<0.001), as well as impaired LV-GLS (−14.0 vs. −19.5%, p=0.012). Eighteen events (12 deaths, 6 HFH) occurred during follow-up (11.4±9.1 months). On multivariable Cox-regression adjusted for baseline, procedural, imaging, and biomarker data, RV but not LV-GLS was significantly associated with outcome (adj.HR 2.50, 95% CI: 1.29–4.86, p=0.007 and 1.46, 95% CI: 0.50–4.28, p=0.491, respectively). Among various definitions of RVD on echocardiography and CMR, only RV-GLS on CMR-FT was significantly associated with outcome (RV-GLS >−20%: adj.HR 7.53, 95% CI: 2.07–27.42, p=0.002), but not RVEF on CMR or echo-indices of RV function (Central Illustration). Follow-up CMR-FT was performed in 21 (34%) patients and RV-GLS significantly improved after TMVR (−20.6 to −25.2%, p=0.016), irrespective of additional TTVR. Conclusions: RV-GLS, as determined on CMR-FT, rather than LV-GLS or RVEF, is an independent predictor of outcome in patients undergoing TMVR. Funding Acknowledgement: Type of funding sources: None.